Broader-Scale Monitoring for Federal Forest Planning: Challenges and Opportunities. Issue 3 (18th March 2019) - Wurtzebach, Zachary; Schultz, Courtney; Waltz, Amy E M; Esch, Bryce E; Wasserman, Tzeidle N
Abstract: Federal land-management agencies are increasingly developing policies to support multiscale monitoring for land-management planning and decisionmaking. Regulations for national forest planning promulgated in 2012 require US Forest Service Regions to develop "broader-scale" monitoring strategies conducted at scales greater than a single planning unit that can complement forest plan monitoring strategies. Given that this requirement is relatively new, we conducted research to investigate the advantages, challenges, and opportunities associated with implementation. We conducted and analyzed interviews with 95 interviewees from forest and regional levels of the agency, and federal, state, nongovernment, and research organizations who could provide insight on broader-scale monitoring challenges and opportunities. We also drew on findings from four interagency workshops. We found that broader-scale monitoring strategies have the potential to generate efficiencies for forest planning processes and improve coordination and communication across levels of the agency and with external partners. Major challenges for implementation relate to limited human and financial resource capacity and the agency's decentralized organizational structure and culture. Opportunities for addressing these issues include building capacity for implementation through partnerships and investing in regional capacity for coordination and implementation.